ANALISIS PENGARUH CURRENT RATIO, EPS, ROA, DER, DAN SIZE TERHADAP INITIAL RETURN PERUSAHAAN YANG MELAKUKAN IPO (Studi kasus pada Perusahaan Go Public Yang Terdaftar di BEI Periode 2008-2011) - Erlina, Iin Puji; Widyarti, Endang Tri (Diponegoro Journal of Management, 2013)
IPO or Initial Public Offering (IPO) is one of the interesting problems  for research in finance. Because, in the initial public offering provides substantial positive returns for investors. Initial returns are influenced by financial and non-financial informations. Many previous studies using financial and non-financial to examine the initial return. However, initial research in this study only uses financial informations to examine the initial return. So that, the data generated in this study only focused on financial information that affects Initial return.  Besides, there are many results of previous studies  are inconsistent. This study aims to analyze the variables of financial information that affects the level of initial returns. The variables studied  include the Current Ratio, Earning Per Share (EPS), Return on Assets (ROA),  Debt to Equity Ratio (DER) and SIZE.This study used purposive sampling method to observational studies and literature as a means  to  collect  data. The    population  of  80  publicly  traded  companies  listed  on  the  Stock Exchange during the study period 2008-2011, the sample obtained by 55 companies. Linear regression analysis used as a method for analyzing the hypothesis in this study.The results of the regression analysis showed that the value of the F-test  for 0.009 <0.05, the model  fits to data. Partially (T-test) only Earning Per Share (EPS) and Return on Assets (ROA) that significantly influence initial return. The value of Adj-Rsquare is 18.8%, thats means that only the initial return of 18.8% can be explained by the five variables of this study